Analisis Ukuran Perusahaan dan Kinerja Maqasid Syariah Terhadap Nilai Perusahaan - Nurul Aisah; Doni Hermansyah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to analyze how company size and Integrated Maqasid Al-Shariah Based Performance (IMSPM) influence company value. This type of research is explanatory research using a quantitative approach. In this research, panel data regression analysis was carried out using the Eviews program. In this research, purposive sampling was used in sampling. And the test results on the model show that the Fixed Effect Model (FEM) was chosen as the estimation model using the Cross-section weights approach estimator. Based on the results of hypothesis testing, it is known that IMSPM has a significant negative effect on company value as measured by EVA, while company size has a significant positive effect